The interaction effects of working capital management on the relationship between key determinants of working capital and firm performance - Choong, Yuen Leng (2016)
The current global economy uncertainties have led to the reduction in the accessibility to trade credit facilities imposed on firms by banks and financial institutions. Critically, firms are keen to look internally to working capital management as a key source of finance. Among the main goal of this research is to evaluate the moderating role of the working capital management on the relationship between key determinants of working capital and firm performance. The population for this study covers manufacturing firms listed on the main market of Bursa Malaysia Securities Berhad. This study covers eleven sectors classification based on the criteria established by Malaysia Investment Development Authority. All data is extracted from Bloomberg database. The multivariate analysis of this study is carried out using Statistical Package for the Social Sciences in order to test the hypotheses. The findings have shown that the relationship between key determinants of working capital and firm performance are moderated by working capital management and they form a contemporary working capital management model. Likewise, days sales outstanding and net liquid balance serves as alternative measures of a firm efficiency and liquidity position. Also, it was found that working capital requirements moderate all the relationships between the key determinants of working capital and firm performance. Except for firm size, it was also found that net liquid balance moderates the relationships between the key determinants of working capital and firm performance. This study concludes that the interaction effects of working capital management in listed manufacturing firms as modifying either the strength or direction of relationships between predictors and criterion. Therefore, it provides a comprehensive research framework for listed manufacturing firms to gain competitive advantage in terms of operational analysis, resource management and profitability.